1978
DOI: 10.1159/000172660
|View full text |Cite
|
Sign up to set email alerts
|

A Micropuncture Study of Glomerular Filtration and Tubular Reabsorption of Endogenous Renin in the Rat

Abstract: Renin concentrations in nanolitre samples of arterial and renal venous plasma and proximal tubular fluid were measured by radioimmunoassay. Clearance methods and occlusion- and transit time techniques were used for estimates of total renal and proximal tubular function. The renin concentration in proximal tubular fluid, when corrected for water reabsorption, declined exponentially along the convoluted segment. 90% of filtered renin was reabsorbed by this segment. The renin concentration of the ultrafiltrate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Micropuncture studies of rat PTs have provided direct evidence that this small protein (36 to 40 kDa) can be found in glomerular ultrafiltrate at a fifth of its plasma concentration and that it is rapidly reabsorbed along the PT. 7 The escape of even a small fraction from such fate could contribute substantially to renin in final urine, however. Although renin may also be synthesized in PTs, 8 this contribution is likely to be small at best, as it is not detected by immunohistochemistry of renal tissue.…”
Section: Lantelme Et Al Urinary Angiotensinogen and Dietary Sodium 1011mentioning
confidence: 99%
See 1 more Smart Citation
“…Micropuncture studies of rat PTs have provided direct evidence that this small protein (36 to 40 kDa) can be found in glomerular ultrafiltrate at a fifth of its plasma concentration and that it is rapidly reabsorbed along the PT. 7 The escape of even a small fraction from such fate could contribute substantially to renin in final urine, however. Although renin may also be synthesized in PTs, 8 this contribution is likely to be small at best, as it is not detected by immunohistochemistry of renal tissue.…”
Section: Lantelme Et Al Urinary Angiotensinogen and Dietary Sodium 1011mentioning
confidence: 99%
“…6 Systemic renin is filtered and reabsorbed in the PT. 7 Although not detected in situ, it may be expressed at low level in the PT. 8,9 We have found that renin was also synthesized and secreted in connecting tubule (CNT).…”
mentioning
confidence: 95%
“…A micropuncture study confirmed that renin concentration in the ultrafiltrate in Bowman's capsule was about 20% of the arterial plasma concentration. 8 Using autoradiographic techniques, we 9 found that intravenously injected IZ5 I-labeled renin accumulated mainly in the renal cortex in mice, particularly in the proximal tubules. Bailie et al, 6 in stop-flow studies in dogs, suggested that filtered renin was reabsorbed in the proximal nephron segment.…”
mentioning
confidence: 95%
“…Recent evidence sug gests that renin may be filtered in the mouse kidney and subsequently pinocytozed in the proximal tubule [28], In addition, Leyssac [16] has suggested that glomerular filtration in the rat removes 5.4% of the renin carried to the afferent arteriole and 16.4% of the net RSR. Accordingly, we attempted to deter mine if the reduction in RSR and the nega tive (V-A) PRA differences observed in our initial experiments correlated with a loss of renin into the urine.…”
Section: Discussionmentioning
confidence: 99%